Recent Developments in Identification of Genuine Odor- and Taste-Active Compounds in Foods - Castro-Mejías, Remedios; Durán-Guerrero, Enrique (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Both aroma and taste are important quality criteria for food products, and they have a great influence on our consumption behaviours. In recent years, a significant increase in the number of studies related to the identification of the characteristic odor- and taste-active compounds of particular foods has been observed.In this book, you can find nine valuable scientific contributions, which deal with the more recent analytical developments for the identification of some compounds responsible for odor and taste in foods such as ham, beer, strawberry, Amontillado sherry wine and others, in order to authenticate them or evaluate the effect of different techniques or making stages on their aroma and taste.